Mediation goes global in Singapore - LIM, George S. C. (Institutional Knowledge at Singapore Management University, 2015)
Singapore has positioned itself as an international dispute resolution hub in Asia by providing a complete suite of services for international arbitration, international litigation and mediation through the Singapore International Arbitration Centre (“SIAC”), the Singapore International Commercial Court (“SICC”) and the Singapore International Mediation Centre (“SIMC”). SICC and SIMC build on Singapore’s reputation for quality legal services, including its status as the most preferred seat of arbitration in Asia and the third most preferred seat of arbitration in the world.[1] They bring more options to parties facing cross-border disputes who need tailored solutions that meet their needs.